A new subterranean Iberian Cephennium with unusually modified metatrochanters (Coleoptera, Staphylinidae, Scydmaeninae) - Jałoszyński, Paweł; Struyve, Tim (Zootaxa, 2016)
Cephennium (Geodytes) gladiator sp. n. is described from north-western Spain (Galicia). This is the first known species of Cephennium (and Cephenniini) with males showing monstrously modified metatrochanters in the form of blade-like projections as long as 3/4 of femora. Similar modifications in Scydmaeninae were known previously only among Oriental and South Pacific Glandulariini. Morphological structures of the new species and its placement in the subgenus Geodytes are discussed.